PEMANFAATAN MEDIA SIMULASI DALAM PEMBELAJARAN SISTEM PEREDARAN DARAH DI SEKOLAH DASAR - Cebeng Alhudayatul Ustadza; Yuni Asih; Siti Inganah (STKIP Subang, 2025)
This study aims to describe the implementation of simulation media in teaching the circulatory system in elementary schools and to analyze student learning outcomes after its application. The background of the research stems from students’ difficulties in understanding the abstract concept of blood circulation, which has often been explained only verbally or through static images. The concept of blood flow involving body organs is frequently difficult to grasp without concrete experiences. Therefore, a simple simulation medium was developed by asking students to arrange papers labeled with organs (heart, lungs, upper and lower body) and simulate the pathways of systemic and pulmonary circulation using oxygen and carbon dioxide cards. The research employed a quantitative descriptive approach with 28 sixth-grade students of SD Muhammadiyah 2 Bojonegoro as subjects. The instruments consisted of independent student worksheets (LKPD) and formative assessments. The learning process was carried out through stages of orientation, teacher demonstration, independent exploration, group discussion, and collective reflection. Data from the LKPD showed an overall average score of 3.29, categorized as good, reflecting students’ ability to place organs correctly, arrange the sequence of blood flow, and understand the basic concept of circulation. Meanwhile, the formative assessment results indicated an average score of 85.49, with the majority of students falling into the Good and Very Good categories, and none in the Poor category. These findings align with constructivist theory, which emphasizes the importance of concrete experiences and visualization in understanding abstract concepts. Simulation media proved effective in enhancing student engagement, strengthening conceptual understanding, and fostering independent learning as well as representational skills. Thus, simulation media is recommended as an innovative learning strategy for science education in elementary schools.